KORELASI LAMA HEMODIALISIS DAN KADAR C-REACTIVE PROTEIN (CRP) PADA PASIEN HEMODIALISIS RUTIN - Nurulhuda Suwandari Ningrum; Mohammad Rudiansyah; Dewi Indah Noviana Pratiwi; Nani Zaitun; Fransiscus Xaverius Hendriyono (Homeostasis, 2022)
Chronic kidney disease (CKD) is structural or functional abnormalities in kidney for more than 3 months so the patient must undergo hemodialysis to assist the kidneys. CKD patients on hemodialysis therapy have persistent inflammation due to their disease. One way to determine inflammation is assess a biomarker in form of c-reactive protein (CRP). This study aims to determine the correlation between hemodialysis duration and CRP levels in routine hemodialysis patients. The research method used is observational analytic with cross-sectional approach. This study involved 100 patients with total of 93 patients who met the inclusion criteria and the sample size were 74 people with total random sampling technique. The results of the study from data that weren’t normally distributed showed the median of hemodialysis duration was 18 months, the median CRP level was 3.25 mg/L, and there was no significant correlation between the hemodialysis duration and CRP levels in routine hemodialysis patients.